2011
DOI: 10.1111/j.1365-2664.2011.01976.x
|View full text |Cite
|
Sign up to set email alerts
|

Accounting for detectability improves estimates of species richness in tropical bat surveys

Abstract: Summary1. Species richness is a state variable of some interest in monitoring programmes but raw species counts are often biased due to imperfect species detectability. Therefore, monitoring programmes should quantify detectability for target taxa to assess whether it varies over temporal or spatial scales. We assessed the potential for tropical bat monitoring programmes to reliably estimate trends in species richness. 2. Using data from 25 bat assemblages from the Old and New World tropics, we estimated detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
84
0
15

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(100 citation statements)
references
References 36 publications
1
84
0
15
Order By: Relevance
“…Our overall detectability of 65% in a single survey agrees well with observations from Meyer et al (2011), who found average detectability with acoustic sampling to be 71% for Neotropical AIB. Both values are substantially higher than the 36-40% observed by Duchamp et al (2006) for temperate North America, which could be related to lower overall bat abundance in higher latitudes or to methodological differences, e.g.…”
Section: Differences In Detectability Affect Occupancysupporting
confidence: 80%
See 2 more Smart Citations
“…Our overall detectability of 65% in a single survey agrees well with observations from Meyer et al (2011), who found average detectability with acoustic sampling to be 71% for Neotropical AIB. Both values are substantially higher than the 36-40% observed by Duchamp et al (2006) for temperate North America, which could be related to lower overall bat abundance in higher latitudes or to methodological differences, e.g.…”
Section: Differences In Detectability Affect Occupancysupporting
confidence: 80%
“…Hence, to calculate species-specific detectability and occupancy, repeated surveys are necessary (MacKenzie et al, 2006). The only acoustic sampling study to date to calculate detectability for Neotropical AIBs found an average detectability of 0.71 (i.e., given its presence, a species is detected in 71% of all sampling events), a value considerably higher than the detectability ranging from 0.25 to 0.58 calculated for other bat trophic guilds through mist netting (Meyer et al, 2011). Thus including detectability can be crucial when estimating the effects of anthropogenic processes on species.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Even in a better sampled biome such as the Atlantic Forest, most studies found local richness values below 30 species (Stevens 2013), but it is known that the biome harbors much more species than that (Paglia et al 2012). Detectability differs largely among bat species (Meyer et al 2011), mainly when a single sampling method is used. Thus, a combination of mist netting and additional sampling methods such as bioacoustic monitoring would probably increase the recorded richness in the area (as in Sampaio et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…As trophic guilds can differ in the way they move and obtain resources, differences in their detectability are expected. Thus, we estimated the proportion of nectarivore species detected in each study (Meyer et al 2011). Because there is no reliable method to measure the absolute population density of bats, we calculated the relative abundance of the nectarivores according to Arita (1993), dividing the number of captures of A. caudifer by the overall number of nectarivores.…”
Section: Abundance and Environmental Suitability Data For Anoura Caudmentioning
confidence: 99%